Creative writing and literary system past and present - Houston, Audrianna (States Academic Press, 2023)
"Literature refers to the written work which can serve as a method of recording, preserving and transmitting knowledge and entertainment. It can also have a social, psychological, spiritual or political role. The system which governs the writing, study, or content of literature is known as creative writing. It encompasses both fictional and nonfictional writing, as well as forms such as novels, biographies, short stories and poems. Some of the prominent elements of creative writing are action, narration, setting, tone and plot. This book brings forth some of the most innovative concepts and elucidates the unexplored aspects of creative writing and its relationship with the literary system. It presents this intriguing subject in the most comprehensible and easy to understand language. The book will serve as a valuable source of reference for graduate and postgraduate students"--Back cover